Observability of Production of tttt quarks at pp-colliders in new physics models - Abdeljali Habjial (JOURNAL OF ADVANCES IN PHYSICS, 2020)
The Standard Model production of four top quarks in the process pp –> tttt at a center-of-mass energy s1/2=13 Tev. The data collected by the ATLAS detector represents an impressive study potential, with an integrated luminosity of around 139 fb-1. In this manuscript, we present the production process of four top quarks at the LHC as well as some new physics models associated with this process. These models are studied in analysis carried. Some preliminary results are presented, in particular those of a new method for estimating background noise due to false leptons developed.